2010
DOI: 10.1016/j.joms.2009.03.066
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of NELL1 and Bone Morphogenetic Protein-2 on Calvarial Bone Regeneration

Abstract: Purpose Most craniofacial birth defects contain skeletal components that require bone grafting. Although many growth factors have shown potential for use in bone regeneration, bone morphogenetic proteins (BMPs) are the most osteoinductive. However, supraphysiologic doses, high cost, and potential adverse effects stimulate clinicians and researchers to identify complementary molecules that allow a reduction in dose of BMP-2. Because NELL1 plays a key role as a regulator of craniofacial skeletal morphogenesis, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 61 publications
0
28
0
2
Order By: Relevance
“…37 In addition, NELL-1 has been described to have combinatorial or synergistic bone-forming effects when combined with BMP2 in various in vivo models, including a nude mouse intramuscular model, rat calvarial defect model, and a rabbit maxillary sinus floor elevation model. [43][44][45] Recently, our laboratory performed preliminary studies geared toward bone regeneration, in which to our surprise we found that NELL-1 also significantly attenuated BMP2-induced inflammation. In this study, we formally investigated whether the growth factor NELL-1 could reduce the inflammation frequently encountered with BMP2 treatment.…”
mentioning
confidence: 71%
“…37 In addition, NELL-1 has been described to have combinatorial or synergistic bone-forming effects when combined with BMP2 in various in vivo models, including a nude mouse intramuscular model, rat calvarial defect model, and a rabbit maxillary sinus floor elevation model. [43][44][45] Recently, our laboratory performed preliminary studies geared toward bone regeneration, in which to our surprise we found that NELL-1 also significantly attenuated BMP2-induced inflammation. In this study, we formally investigated whether the growth factor NELL-1 could reduce the inflammation frequently encountered with BMP2 treatment.…”
mentioning
confidence: 71%
“…Although BMP-2 and BMP-7 may represent the initial choice for gene delivery, more potent proteins were recently identified that may allow for a greater response with lower amounts. (129) Because of the crucial role of vascularization in new bone formation, angiogenic proteins can enhance bone formation. (130) In particular, VEGF (131) and bFGF (132,133) have been shown to be beneficial on their own for osteogenesis and in combinations with BMPs.…”
Section: Perspectivementioning
confidence: 99%
“…(146,147) NEL-like molecule-1 (Nell-1) is another molecule under investigation for its osteogenic properties in repair of large segmental defects. (148)(149)(150) Nell-1 was shown to be as effective as BMP-2 in repair of critical-size defect (151) and also works synergistically with BMPs (129) that are endogenously expressed at the defect site. These proteins and, their combinations, are expected to provide further leads in aiding or even replacing BMPs in functional bone regeneration.…”
Section: Perspectivementioning
confidence: 99%
“…Specifically, NELL-1 is a 700kDa protein recognized as a potent pro-osteogenic cytokine and was most often studied for its local bone-forming effects [17][18][19][20][21][22][23][24]. NELL-1 has been reported to induce robust osseous healing of critical-sized rat femoral segmental and calvarial defects [17,25,26], and also to promote lumbar spinal fusion in rats, sheep [21][22][23], and non-human primates. Additionally, NELL-1 has been identified not only to demonstrate anti-osteoclastic effects both in vitro and in vivo [19], but also to suppress adipogenesis [27].…”
Section: Introductionmentioning
confidence: 99%